2010
DOI: 10.1016/j.otsr.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Knee arthrodesis using a vascularised fibular rotatory graft after tumor resection

Abstract: Knee arthrodesis after tumor resection is a complex technique. Septic complications and mechanical failure are frequent regardless of the technique employed. They are related to the extent of bone sacrifice but also to that of soft tissues. The use of vascularised fibula alone and stabilisation by external fixation were the main shortcomings in this series. TYPE OF STUDY RETROSPECTIVE: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In this study, the patients who underwent resection arthrodesis reconstruction had a worse functional outcome than those who underwent osteoarticular allograft, which aligns with previous reports 31,32 . Patients with resection arthrodesis in our series had a lower function and emotional acceptance score compared to patients who underwent osteoarticular allograft reconstruction.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the patients who underwent resection arthrodesis reconstruction had a worse functional outcome than those who underwent osteoarticular allograft, which aligns with previous reports 31,32 . Patients with resection arthrodesis in our series had a lower function and emotional acceptance score compared to patients who underwent osteoarticular allograft reconstruction.…”
Section: Discussionsupporting
confidence: 89%
“…esection of tumours of the femur and tibia around the knee and ankle joints results in large bony defects. [1] While prosthesis offers a reconstructive option, [2] often arthrodesis is an alternative; in case, adequate functional motors cannot be preserved or due to economic constraints (for those patients who cannot afford megaprosthesis). In an immunocompromised patient, the potential for infection and non-union increases if a non-vascularised bone graft is used.…”
mentioning
confidence: 99%
“…The earliest biologic arthrodeses were performed using external fixation systems, intramedullary devices, and hybrid methods with union rates from 38% to 100% and different complications [1,13,17,19,22,24,32,33,36,45,48]. Vascularized fibulae have been used to augment arthrodesis reconstructions of all types with overall excellent results [29,31,37,46]. Septic knee arthritis and failed, septic TKA often require débri-dement of large volumes of bone, necessitating structural intercalary segments to maintain limb length when arthrodesis is performed [25].…”
mentioning
confidence: 99%
“…However, we did not observe a significant difference between failure rates of primary arthrodeses for tumors compared with revision procedures of a prior implant with segmental bone loss. Although success rates of 80% to 100% have been reported after primary, biologic arthrodesis in patients without prior TKA [9,14,19,30,31,37,44], the success rate of arthrodesis performed in patients with an infection at the site of a TKA has been reported to be much lower [8]. However better results in terms of complication rates have been reported using metal implants than biologic reconstruction [2,8,9,11,13,23,33,42,45,47].Whereas Gosheger et al reported no infections in three arthrodeses with the MUTARS 1 implant [16] and Bartlett et al reported one infection in 10 Stanmore implants [3], there were nine infections in our 31 patients.…”
mentioning
confidence: 99%